2022
DOI: 10.1093/bjsopen/zrac063
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-early initiation of postoperative rehabilitation in the post-anaesthesia care unit after major thoracic surgery: case–control study

Abstract: Background Physiotherapy is a major cornerstone of enhanced rehabilitation after surgery (ERAS) and reduces the development of atelectasis after thoracic surgery. By initiating physiotherapy in the post-anaesthesia care unit (PACU), the aim was to evaluate whether the ultra-early initiation of rehabilitation (in the first hour following tracheal extubation) would improve the outcomes of patients undergoing elective thoracic surgery. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In patients who are obese, the use of volatile anaesthetic agents has been reported to reduce the time it takes for patients to become fully awake, but this reduction may not be considered clinically significant and remains a topic of debate [37, 38]. Lastly, a recent study conducted in our institution suggested the feasibility of very early initiation of postoperative rehabilitation in the post‐anaesthesia care unit following major thoracic surgery after general anaesthesia with TIVA [39]. Nevertheless, the superiority of TIVA vs. volatile‐based techniques remains controversial, and there are currently two major studies investigating this issue [40, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who are obese, the use of volatile anaesthetic agents has been reported to reduce the time it takes for patients to become fully awake, but this reduction may not be considered clinically significant and remains a topic of debate [37, 38]. Lastly, a recent study conducted in our institution suggested the feasibility of very early initiation of postoperative rehabilitation in the post‐anaesthesia care unit following major thoracic surgery after general anaesthesia with TIVA [39]. Nevertheless, the superiority of TIVA vs. volatile‐based techniques remains controversial, and there are currently two major studies investigating this issue [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent study conducted in our institution suggested the feasibility of very early initiation of postoperative rehabilitation in the post-anaesthesia care unit following major thoracic surgery after general anaesthesia with TIVA [39]. Nevertheless, the superiority of TIVA vs. volatile-based techniques remains controversial, and there are currently two major studies investigating this issue [40,41].…”
Section: Kotani Et Al Reported a 10% Increase In Mortality Withmentioning
confidence: 99%